The introduction in abstract writing of term papers: rhetorical moves and linguistic realizations - Chuah, Ek Lon; Tan, Helen; Swee, Heng Chan; Abdullah, Ain Nadzimah (Academy of Language Studies, Universiti Teknologi MARA, 2012)
In past investigations on research articles, there have been various focuses – acknowledgement, abstract, introduction, method, results, discussion, and conclusion (for example, Swales,1990; Giannoni, 2002; Hwa Lim, 2006; Williams ,1999; Peacock, 2002; Hirano, 2009; Pho, 2008 and Samraj, 2005) These investigations have focused on published materials in journals. This research aims to investigate rhetorical moves and linguistic realizations in the introduction of 100 abstracts found in students’ scientific term papers. They are written parallel to a research report which in effect reflects the essence of journal article writing. The rhetorical moves investigated are focused only on the introduction section of the abstract which plays a significant role in attracting reader’s attention and giving some background that will motivate him to read further. The analysis of the introduction in abstract writing uses an adaptation of Cava’s model (2007) of rhetorical moves and the linguistic realizations are analyzed following an adaptation of Hyland’s framework (2005). In identifying linguistic realizations, a concordance tool MP2.2 is used. Findings are presented to show the manifestations of moves in the introduction of abstract writing to identify the characteristic patterns with a discussion on the linguistic realizations that accompanied the moves. This study would provide pedagogical implications for the ESP classroom which has a focus on academic writing, with particular reference to research report writing that appears to be a necessary skill for tertiary students and beyond.